Measurement of Goodwill as an Intangible Asset in Accounting - Panjaitan, Gloria Oktavania; Athaya, Nada Syifa; Tamba, Rani; Safitri, Tsamara Nayla; Aliah, Nur (Jurnal Bisnis Mahasiswa, 2024)
This study aims to analyze the method of measuring goodwill as an intangible asset in accounting. Goodwill is an important element in the total value of a company resulting from an acquisition or business combination and is recognized as an intangible asset. Determining the value of goodwill often faces challenges due to factors that are difficult to measure, such as reputation, customer loyalty, and management quality. This research examines intangible asset measurement theory, relevant accounting standards, as well as methods commonly used in practice, such as the cost method, fair value, and future net income analysis. The research method used is an in-depth literature study on the concept and measurement of goodwill as an intangible asset in accounting. The results show that the choice of goodwill measurement method has a significant effect on the company's financial reporting, especially on the value of assets and equity. This research emphasizes the need to develop more accurate and consistent accounting standard guidelines in the measurement of goodwill.